Entrevista a la economista Loretta Napoleoni, autora de Economía Canalla: la nueva realidad del capitalismo - Mourenza, Andrés (La Sociología en sus Escenarios, 2010)
Abstract. The Italian economist Loretta Napoleoni is one of the authors more critics with western financial Capitalism. In his last book he assures that the Chinese Communists are better capitalists than we western them. Our Capitalism is a Capitalism of services and financier without the necessary controls, which has ended at the creation of a series of financial bubbles. Capitalism is a system based on the operation of the resources and the work is a resource. How the western capitalist system would recover of the crisis if we do not produce anything? We must return to produce, Napoleoni said. In another one of its books, "Economy Gangster", assures that one of the solutions to the western economic crisis is the Islamic finances. Resumen. La economista italiana Loretta Napoleoni es una de las autoras más críticas con el capitalismo financiero occidental. En su último libro asegura que los comunistas chinos son mejores capitalistas que nosotros los occidentales. Nuestro capitalismo es un capitalismo de servicios y financiero sin los controles necesarios, lo que ha desembocado en la creación de una serie de burbujas financieras. El capitalismo es un sistema basado en la explotación de los recursos y el trabajo es un recurso. ¿Cómo el sistema capitalista occidental se recuperara de la crisis si no producimos nada? Debemos volver a producer, responde Napoleoni. En otro de sus libros, Economía canalla, asegura que una de las soluciones a la crisis económica occidental son las finanzas islámicas.